Relationship Education for Incarcerated Adults. Issue 1 (14th July 2015) - Harcourt, Kate Taylor; Adler‐Baeder, Francesca; Rauer, Amy; Pettit, Gregory S.; Erath, Stephen
Abstract : As relationship education (RE) programs become more widely implemented, it is important to measure and document the changes associated with RE for diverse audiences. Also, researchers have been challenged to examine the impact of RE with more disadvantaged groups. While we are seeing an increase in this area, only three studies have examined RE with an incarcerated sample. These previous studies examined only those currently in a relationship and focused primarily on couple functioning. The aim of this study was to expand the existing literature by examining RE with a broader sample of incarcerated adults, regardless of current relationship status, and to expand our understanding of its association with outcomes beyond the couple domain by also including measures of individual and parental functioning. In addition, we examined whether change from pre‐ to posttest was moderated by individual characteristics. Using a sample of incarcerated adults ( N  = 122), the study found positive change in three domains of functioning (couple, individual, and parental). Specifically, results indicated change on five of the eight outcome variables examined. Overall, we found both similarities and differences among program participants on changes from pre‐ to posttest. For the majority of outcomes, the positive change from pre‐ to posttest emerged regardless of individual characteristics.